Enhancement of Chromatin and Epigenetic Reprogramming in Porcine SCNT Embryos—Progresses and Perspectives - Glanzner, Werner Giehl; de Macedo, Mariana Priotto; Gutierrez, Karina; Bordignon, Vilceu (Frontiers in Cell and Developmental Biology, 2022)
Over the last 25 years, cloned animals have been produced by transferring somatic cell nuclei into enucleated oocytes (SCNT) in more than 20 mammalian species. Among domestic animals, pigs are likely the leading species in the number of clones produced by SCNT. The greater interest in pig cloning has two main reasons, its relevance for food production and as its use as a suitable model in biomedical applications. Recognized progress in animal cloning has been attained over time, but the overall efficiency of SCNT in pigs remains very low, based on the rate of healthy, live born piglets following embryo transfer. Accumulating evidence from studies in mice and other species indicate that new strategies for promoting chromatin and epigenetic reprogramming may represent the beginning of a new era for pig cloning.